Cytogenetic Characterization of Seven Novel satDNA Markers in Two Species of Spined Loaches (Cobitis) and Their Clonal Hybrids - Marta, Anatolie; Dedukh, Dmitry; Bartos, Oldrich; Majtanova, Zuzana; Janko, Karel (Genes, 2020)
Interspecific hybridization is a powerful evolutionary force. However, the investigation of hybrids requires the application of methodologies that provide efficient and indubitable identification of both parental subgenomes in hybrid individuals. Repetitive DNA, and especially the satellite DNA sequences (satDNA), can rapidly diverge even between closely related species, hence providing a useful tool for cytogenetic investigations of hybrids. Recent progress in whole-genome sequencing (WGS) offers unprecedented possibilities for the development of new tools for species determination, including identification of species-specific satDNA markers. In this study, we focused on spined loaches (Cobitis, Teleostei), a group of fishes with frequent interspecific hybridization. Using the WGS of one species, C. elongatoides, we identified seven satDNA markers, which were mapped by fluorescence in situ hybridization on mitotic and lampbrush chromosomes of C. elongatoides, C. taenia and their triploid hybrids (C. elongatoides × 2C. taenia). Two of these markers were chromosome-specific in both species, one had centromeric localization in multiple chromosomes and four had variable patterns between tested species. Our study provided a novel set of cytogenetic markers for Cobitis species and demonstrated that NGS-based development of satDNA cytogenetic markers may provide a very efficient and easy tool for the investigation of hybrid genomes, cell ploidy, and karyotype evolution.
Keywords: druhová specificita; Reproduction, Asexual; karyotypizace; hybridizace in situ fluorescenční; Karyotyping; karyotyp; nepohlavní rozmnožování; Species Specificity; klonální evoluce; Cypriniformes; satelitní DNA; Animals; DNA, Satellite; zvířata; Clonal Evolution; Hybridization, Genetic; máloostní; In Situ Hybridization, Fluorescence; hybridizace genetická; Karyotype